Oxford illustrated Shakespeare dictionary - Crystal, David, 1941-; Crystal, Ben; Bellamy, Kate (Illustrator) (UK: Oxford University Press, 2015)
The Oxford Illustrated Shakespeare Dictionary is the first of its kind, a brand new illustrated alphabetical dictionary of all the words and meanings students of Shakespeare need to know. Every word has an example sentence selected from the twelve most studied plays including Macbeth, Hamlet, Romeo and Juliet, A Midsummer Night's Dream, and Henry V. Usage notes and theatre notes provide additional background to Shakespearean times and the performance of his plays. Further support is provided by language panels on select topics like the humours, swearing, and stage directions, and full-colour illustrated thematic spreads on special feature topics from clothes and armour to music and recreation. The dictionary is easy to use with its clear signposting, accessible design, and expertly levelled contemporary look and feel. It is the perfect support for a full understanding of Shakespeare, created by renowned authors Professor David Crystal and actor Ben Crystal, a father and son team who combine for the first time the academic and the theatre, bringing together language, literature, and lexicography in this unique Shakespeare dictionary of global appeal.
Keywords: Shakespeare, William, -- 1564-1616 -- Dictionaries; Shakespeare, William, -- 1564-1616 -- Language -- Glossaries, etc; Shakespeare, William, -- 1564-1616.; 1500 - 1700; English language -- Early modern, 1500-1700 -- Dictionaries; Picture dictionaries; English language -- Early modern; Language and languages; Picture dictionaries; Dictionaries; Glossaries, vocabularies, etc